Factors determining the economic performance of Litopeneaus vannamei (whiteleg shrimp), aquaculture in Tamil Nadu, India. (28th June 2022) - Durai, V.; Lloyd Chrispin, C.; Bharathi, S.; Velselvi, R.; Karthy, A.
Abstract: Shrimp aquaculture has gained significant attention to meet the animal protein need of the growing world population and is widely cultured in semi‐intensive methods around the world including India. Here, we examined the growth performance and enterprise budget of shrimp farming using field‐level survey data from 194 farms in Tamil Nadu for successive two crops of a year. An estimated shrimp production was 5880 kg/ha/crop from an average pond size of 2.93 ha and stocking density of 39 numbers m −2 for a culture period of 92 days. Similarly, in terms of feed, a total of 9117 kg/ha/crop was found to be used with an average food conversion ratio of 1.55 kg. An initial capital investment requirement of USD $ 22062.11 was observed. The fixed cost of USD $ 2984.21 and variable cost of USD $ 40685.13 were recorded in the production process of shrimp. The harvested shrimp quantity (5880 kg/ha/crop) generated gross revenue of USD $ 50405.56 ha/yr. The calculated net revenue for the shrimp farms of Tamil Nadu was USD $ 6736.22. The Cobb–Douglas production function results showed that water salinity, culture days, stocking density, quantity of feed used, shrimp harvest size, harvest count, daily weight gain, specific growth rate and survival rate was positively influencing the economic performance of the shrimp but not statistically significant. Whereas, the food conversion ratio statistically negatively influenced the economic performance of shrimp production in Tamil Nadu.